Effective Adsorption of Harmful Herbicide Diuron onto Novel Activated Carbon from Hovenia Dulcis - Sepúlveda-Ortiz, P; Sepúlveda-Ortiz, P (Elsevier B.V., 2022)
A porous activated carbon from Hovenia dulcis was prepared using zinc chloride (ZnCl2) as an activating agent and applied to remove diuron in aqueous solutions. The carbon presented a smooth and regular surface, with an area of 898 m² g−1, narrow pores of average diameter equal to 1.242 nm, and volume of 0.296 cm3 g−1. Adsorption was favored by increasing the pH and temperature. Isothermal curves formed a characteristic plateau of the Langmuir monolayer isotherm. Thermodynamic results indicated that herbicide adsorption was spontaneous, favorable, and endothermic (ΔH0 = 35.9093 kJ mol−1). The decay of the diuron concentration displays that equilibrium is attained in 120 min. The best results were obtained at pH 6, temperature of 328 K and 200 rpm and C0 of 200 mg·L−1. Langmuir model had the best adjustment, obtaining maximum adsorption capacity of 96.68 mg·g−1. Pore volume and surface diffusion model (PVSDM) was suitably represent the decline comportment of diuron. The adsorption mechanism was rate controlled by the external and internal mass transfer. In the treatment of a river water sample contaminated with diuron, activated carbon revealed high performance, reaching 95% removal of the emerging pollutant. © 2022 Elsevier B.V.